The Historicity of the Economic Verses on Fatwa of DSN-MUI about Sharia Electronic Money - Athoillah, Mohamad Anton; Mohd Nor, Mohd Roslan; Khoiruddin, Heri; Rohimin, Rohimin (Jurnal Ilmiah Peuradeun, 2021)
In the Quranic revelations period, the electronic money has not been known yet, but the National Sharia board-Indonesia Council of Ulama (DSN-MUI) has issued a fatwa and referred to the Quranic verses as one of its legal bases. The fatwa mentioned is fatwa Number: 116/DSN-MUI/IX/2017 about Sharia Electronic Money. This fatwa said that sharia electronic money is electronic money suitable with sharia principles. The verses in this fatwa were analyzed based on the historical background of revelation, to find out whether the legal basis for the fatwa is the verses related to economic activities or not. This study showed that the Quranic verses used as a legal basis for a fatwa on the sharia electronic money were not only the verses revealed in relation with the economic activity or the verses in which economic activity was implied, but also the Quranic verses revealed in relation with other activity in which the Islamic principles were implied, and then those Islamic principles have been applied in a fatwa about sharia electronic money.